Managing resettlemnt in India: approaches, issues, experiences - Mathur, Hari Mohan (ed.) (New Delhi, 2006)
This volume of essay looks at how Indian society takes care of the people whom development and large scale infrastructure projects have displaced. Displacement causes migration, impoverishment, and great upheaval in the social fabric. In a word, displacement hurts. The 14 essays in this volume identify significant solutions towards resettlement which can be implemented in unique and diverse displacement contexts to mitigate suffering and to enhance environmental sustainability. They identify existing lapses in resettlement management and procedures and formulate useful policy responses. They pay specific attention through a wide variety of examples to the socio economic consequences of development projects, policy and legal issues, planning and management issues.
Keywords: Resettlement management